Effects of Atractylon on Proliferation and Apoptosis of Intestinal Cancer Cells Through PI3K/AKT/mTOR Signaling Pathway: Effects of Atractylon on intestinal cancer cells - Mao, Junjun; Wang, Xinping; Yu, Minghui; Sun, Chenkun (Cellular and Molecular Biology, 2022)
The study aimed to explore the effects of atractylon on the proliferation and apoptosis of intestinal cancer cells through the phosphatidylinositol 3-hydroxy kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathway. The intestinal cancer HT29 cell lines were cultured in vitro, and atractylon at different concentrations (15 and 30 mg/mL) was added. Then cell proliferative activity was detected via cell counting kit-8 (CCK8) assay, and the proportion of positive cells was determined using EdU staining. The content of interferon-γ (INF-γ), tumor necrosis factor-α (TNF-α) and matrix metalloproteinase-9 (MMP-9) was detected via enzyme-linked immunosorbent assay (ELISA), and the apoptosis of HT29 cells was detected through terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining. Moreover, reverse transcription-polymerase chain reaction (RT-PCR) was performed to determine the messenger ribonucleic acid (mRNA) levels of proliferation, apoptosis and PI3K/AKT/mTOR signaling pathway-related genes, and Western blotting was used to analyze the expression of the PI3K/AKT/mTOR signaling pathway. The cell growth status was poorer with a lower density in the 15 mg/mL atractylon group and basically normal morphological structure in the 30 mg/mL atractylon group. The number of cells significantly declined and the proliferative activity was also significantly weakened in the 30 mg/mL atractylon group. There were obviously more apoptotic cells in the 30 mg/mL atractylon group. Besides, INF-γ, TNF-α and MMP-9 were all evidently decreased in the 30 mg/mL atractylon group. Expressions of B-cell lymphoma-2 (Bcl-2), PI3K, AKT and mTOR obviously declined in the 30 mg/mL atractylon group, and they were raised in the NC group, while the expression of Caspase3 showed the opposite trends. Atractylon at an appropriate concentration can inhibit the proliferation and promote the apoptosis of intestinal cancer cells by suppressing the PI3K/AKT/mTOR signaling pathway, which can be used to treat colorectal cancer and other related diseases.